Improved pork products for the 1990's - Kropf, Donald H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The word "improved" in a commercial sense means "altered product characteristics to meet the consumers' real and perceived needs." The pork industry in the 90's must progress toward offering products designed to meet consumer demands instead of saying "this is what we are producing and you'd better buy it." For the pork producer, "improved" means those products that will. increase pork sales. We must realize that the primary nutritional contributions of pork to human diets will be protein and vitamins, especially B-vitamins. Perhaps we should emphasize these more in our advertising, but good flavor, low fat, low salt, and convenience are likely the selling points to be emphasized. Perhaps we also can stress the desirability of other features of new pork products developed in the 90's, such as added dietary fiber or the advantage of pork fat in having a more desirable ratio of polyunsaturated/monounsaturated fatty acids in relation to saturated fatty acids than other animal fats and some plant fats.
Keywords: Swine; Pork products; Bellies; Sausage; Deli; Carcass leanness